The Effect of English Language Proficiency Level on Undergraduate Libyan Students’ Use of Subject Verb Agreement - Elmejie, Eman; Elzawawi, Fatima; Msimeer, Amel ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2021)
This study aims to examine the proficiency level of Libyan EFL (English as a Foreign Language) undergraduate students in terms of the types of subject-verb agreement errors they commit. It also attempts to identify, analyze and categorize the frequency errors related to subject-verb agreement into three categories. These errors are statically analyzed and classified into: subject-verb agreement (SVA) errors with third person singular subjects (TPSS), with third person plural subjects (TPPS), with compound subjects (CS). The participants of this study were 40 intermediate and advanced students whose major is English at the Faculty of Arts in Misurata University, Libya. They were chosen based on their level of English language proficiency during the current study. The data of this study were collected through a written test consisting of six short passages. The results showed that the percentage of errors made by both groups was below 30% which refers to non-significant differences among the two groups with respect to the SVA errors made by them. Consequently, it can be concluded that language proficiency has little effect on the participants' use of the SVA rule. It was also found that subject-verb agreement errors with (TPPS) were the least frequent, and the most common errors committed were (CS) and (TPSS). This study is important for EFL teachers to be aware of the subject verb agreement errors that their target learners commonly produce. The implications for SLA research and classroom teaching practice are given for foreign language teachers and researchers.